Wish You Were Here? Quasi-Experimental Evidence on the Effect of Education on Attitude toward Immigrants - Beatrice d'Hombres; Luca Nunziata (Institute for the Study of Labor (IZA), 2015)
We use European Social Survey and Labour Force Survey data to estimate the causal effect of education on European natives' opinion toward immigration exploiting reforms in compulsory education in Europe in the 1960s through the 1990s. Our findings show that higher education leads to a more positive attitude toward immigrants. We also investigate the mechanisms behind the effect of education on attitudes by evaluating both economic and non-economic channels. We find that higher education places individuals in occupations that are less exposed to the negative externalities of migration, although not in sectors/occupations where the share of migrants is necessarily smaller, suggesting that migrants and low-educated natives are complementary rather than substitutes in the labour market. In addition, education alters values and the cognitive assessment of the role of immigration in host societies, with a positive effect on tolerance of diversity and a positive effect on the assessment of immigration's role in host countries. Our findings suggest that education as a policy instrument can increase social cohesion in societies that are subject to large immigration flows.
Keywords: I20; J61; J15; 330; immigration; attitude towards immigrants; perception; education; compulsory education reforms